Screening of sunflower genotypes for drought tolerance with PEG 6000 - N.K. GAYATHRI; S.M.D. RAFI (Seed Research, 2026)
A study was conducted at Regional Agricultural Research Station (RARS), Nandyal during Kharif 2010 to screen the sunflower entries LDM 02, ARM 239 B, CMS 852 B, IB-5, 136-R, NDR-71, CMS 23 B, CMS 40 B, CMS 17 B, ARM 242 B, 150-R for drought tolerance with PEG 6000. The results showed that CMS 17 B recorded higher germination (93.33%), seedling length (11.56 cm) and seedling dry weight (7.525 g). High Promptness Index (PI = 4.096) and Root Length Stress Tolerance Index (RLSI = 79.53) were recorded by LDM 02 and Germination Stress Tolerance Index (GSI = 255.9) and Dry Matter Stress Tolerance Index (DMSI = 380.94) were by CMS 23 B. With increase in PEG concentration from 5 to 15% there was decrease in germination, seedling length, seedling dry weight and other parameters. In the analyses of interaction effects it was clearly shown that genetic variation is useful to develop cultivars suitable to arid and semi-arid zones. From this study, on the basis of DMSI values, which are considered as reliable indicator of drought tolerance in sunflower, the inbred lines CMS 23 B and CMS 40 B and CMS 17 B were grouped as best lines, IB-5 and LDM 02 as medium lines and remaining as sensitive to drought condition.